In vitro antioxidant and anticancer potential of intra-cellular ethyl acetate extract of marine-derived fungus Talaromyces tratensis SS10 - Shabana, S.; Bhargavi, R. Venkata; Satya, A. Krishna (Journal of Phytology, 2024)
Marine fungi are well-known for producing structurally distinct secondary metabolites, making them potential sources of novel therapies. The present investigation aims to study the in vitro antioxidant and anticancer potential of intra-cellular crude ethyl acetate extracts of Talaromyces tratensis SS10. In the present study, qualitative and quantitative phytochemical studies of various solvent extracts of T. tratensis have been carried out using standard protocols. Later, ethyl acetate extract of T. tratensis was analyzed for phytochemicals using Gas Chromatography Mass Spectrometry (GC-MS). Further, the antioxidant properties of the T. tratensis ethyl acetate extract have been done by Ferric reducing antioxidant power assay (FRAP). Further, the anticancer potential of this extract has been carried out by MTT assay against human cancer cells such as MDA MB 231, HeLa, and HT-29. Ethyl acetate exhibited a higher yield of chemical extraction than the other solvents used. The GCMS analysis of T. tratensis ethyl acetate extract revealed major phytoconstituents such as N-(1,1-Dimethylpropyl)-2,2,3-trimethylaziridine-1-carboxamide, 1-Undecanol, 5,5 Dimethyl-3-vinyl cyclohex-2-en-1-one, 1,2-Benzenedicarboxylic acid, bis (2-methyl propyl) ester. T. tratensis ethyl acetate extract showed the highest percentage of Fe3+ reduction (48.093±1.469%) at 120 μg/mL, with an IC50 value of 157.26 μg/mL concentration. Furthermore, 100 μg/mL of the extract showed significant cell death rates in cytotoxic assays, indicating a low percentage of viable cells for all three examined cell lines. The T. tratensis ethyl acetate extract has shown a dose-dependent cytotoxic effect against all tested cancer cell lines. The better IC50 value (6.25 μg/mL) was recorded in the case of HeLa cell lines followed by 12.5 μg/mL for both MDA MB 231 and HT-29 cell lines. The presence of bioactive compounds such as Benzeneethanamine, N-[(pentafluorophenyl)methylene]-beta.,3,4-tris[(trimethylsilyl) oxy]-, 1,2-Benzenedicarboxylic acid, bis(2-methylpropyl) ester, and cyclononasiloxane, octadecamethyl- may have contributed to the ethyl acetate extracts’ strong antioxidant and anticancer properties. The current study’s findings show that T. tratensis SS10 has the potential for drug development due to its chemical constituents, which possess various biological activities.